2009
DOI: 10.1186/1472-6831-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications of pediatric dental general anesthesia procedure provided in Jeddah hospitals, Saudi Arabia

Abstract: Background: Review of post-operative morbidity reports for pediatric dental care under general anesthesia (GA) show great variations. Until now, no morbidity data has been available to estimate the safety of pediatric patients under GA for dental rehabilitation in Saudi Arabia. The purposes of this study were to (1) investigate post-operative complications associated with dental care under GA and (2) correlate morbidity reports with patient's characteristics, dental procedures, and hospital protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
60
6
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(102 citation statements)
references
References 20 publications
12
60
6
8
Order By: Relevance
“…The postoperative complications studied decreased in severity and frequency over the 72 h of the study, both in ASA I patients and in ASA II‐III patients, without significant differences between the groups. There was a high presence of one or more complications at 24 h, equaling 85.7% in ASA I patients and 85.7% in ASA II‐III patients, which is similar to other authors who found it to be 98.8%, irrespective of ASA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The postoperative complications studied decreased in severity and frequency over the 72 h of the study, both in ASA I patients and in ASA II‐III patients, without significant differences between the groups. There was a high presence of one or more complications at 24 h, equaling 85.7% in ASA I patients and 85.7% in ASA II‐III patients, which is similar to other authors who found it to be 98.8%, irrespective of ASA.…”
Section: Discussionsupporting
confidence: 87%
“…There are few scientific publications on postoperative morbidity following GA. The one publication that exists is quite varied in terms of recording the different signs and symptoms, making the data analysis confusing due to the many variables 10 . Children undergoing dental rehabilitations under general anesthesia commonly experience postoperative symptoms such as pain, agitation, need for analgesics, and sleepiness.…”
Section: Introductionmentioning
confidence: 99%
“…33 The early hours exhibit the most pain. Moderate-to-severe pain appears to peak at 2 hours, then reduces in intensity over the 3-day period, a trend which is consistent in morbidity studies focusing on pediatric dental surgery under GA. 18,19,22 The prevalence of 42.3% by PPPM scores was highest at home arrival. However, interpretability of this score at this period is difficult because some of the PPPM items required a longer duration of observation.…”
Section: Discussionmentioning
confidence: 98%
“…13,14,16 In the study by Atan et al, 13 postoperative pain was reported in 74% of children aged 6 to 16 years following dental treatment under intubated GA. Of the morbidity measures reported, pain had the longest duration in comparison to sleepiness, weakness, and nausea. Farsi et al 18 determined that the prevalence of postoperative pain was 47.8% at 36 hours and 16.7% at 72 hours. The pilot study by Fung et al 15 found that 57.5% of 40 children who had 1 or more extractions under GA had postoperative pain immediately after treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation